(untitled) (Journal of history, 2022)
Annotation. In Soviet Russia, Geology was the most advanced science in the world. After the formation of the USSR, there was a great need for geological research. So, the implementation of the industrialization program directly depended on minerals and raw materials. 25 thousand ore deposits were opened in the Union, including about 2 thousand that became the main pillars of the country’s economy. These facts show what a powerful force there was in Soviet Geology. The article reveals the history of the Torlan mountain range in geological terms during the Soviet period. Thanks to the study of Karatau deposits, the Soviet geological school has risen to a new level. Especially in the 1920s and 1930s, new ore deposits were discovered that had not previously been the object of research. The article reveals the Imperial identity in the activities of Russian geologists who came for consideration under special state orders. Keywords: Ashchysay, Karatau, geology, unique, the researchers, the Soviet Empire, ore, lead, pits.